Morphology and formation of crystalline leucine microparticles from a co-solvent system using multi-orifice monodisperse spray drying. Issue 8 (22nd June 2021) - Wang, Zheng; Ordoubadi, Mani; Wang, Hui; Vehring, Reinhard
Abstract: The purpose of this study was twofold: to investigate leucine crystallization kinetics in co-solvent spray drying for a deeper understanding of the morphology and formation process of spray-dried crystalline particles, and also to develop multi-orifice plates using gallium focused ion beam milling in order to increase the production rate of monodisperse spray drying. A monodisperse spray drying technique using a vibrating orifice atomizer equipped with a gallium focused ion beam-manufactured dual-orifice plate was used to produce model particles in this study. The dual-orifice plate achieved an average production rate of 23.8 ± 2.0 mg/hr for the model particles, which allowed sufficient production of monodisperse powders for microscopic and spectroscopic analysis as well as fragility testing, within a reasonable spray drying time period. Leucine was dissolved in a water-ethanol co-solvent at ratios of 0.25/0.75 w/w, 0.5/0.5 w/w, and 1/0 w/w, and then spray dried at inlet temperatures of 20, 40, and 80 °C. Crystallinity of the spray-dried particles was confirmed by Raman spectroscopy. Numerical models were used to predict the crystallization and drying kinetics for the different co-solvent ratios and drying temperatures. Increasing the time available for crystallization correlated qualitatively with a larger crystal size. Changes in particle morphology affected the fragility of the particles, as illustrated in electron microscope images. This work highlights the importance of controlling crystal size and particle morphology via solvent environment and drying temperature in the design and manufacture of microparticles for desired powder properties. Copyright © 2021 American Association for Aerosol Research